Alterations of cholesterol lowering-related proteins in the serum of hypercholesterolemic-induced rats treated with Ficus deltoidea - Chuo, Peck Ham; Fatima Uzar,; Puteri Shafinaz Abdul-Rahman,; Noorlidah Abdullah,; Norhaniza Aminudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cardiovascular disease (CVD) is one of the major non-communicable diseases causing cardiac dysfunction and heart failure. In Malaysia, hypercholesterolemia or high blood cholesterol is known as CVD’s main risk factor. Currently, there is a paradigm shift of interest in Eastern medicines as alternative prevention approaches and therapeutic cholesterol control treatment. Ficus deltoidea (Mas Cotek) is amongst the eastern medicinal plants traditionally consumed either as prevention or treatment for various diseases such as hypertension, diabetes and hypercholesterolemia. This study utilised the proteomic application in determining the changes in a series of proteins that are being differentially expressed in response to F. deltoidea treatment of hypercholesterolemic-induced rats. Identification and quantification of proteins were conducted by using quantitative techniques, wherein two dimensional gel electrophoresis (2D-GE) along with Progenesis Samespots image analysis software and Matrix-assisted laser desorption/ionization Time-of-flight/Time-of-flight (MALDI ToF/ToF) mass spectrometry were utilised. Our results demonstrated that 14 protein spots had displayed alteration in their abundance at a minimum of 1.5 fold. Majority of these identified proteins were involved in lipid metabolism and immune system processes. These variables include apolipoprotein A1 (Apo A1), apolipoprotein E (Apo E), retinol binding protein 4 (RBP4), haptoglobin (HP), complement factor C3 (C3), complement factor C1s (C1s), transthyretin (TTR), ectonucleotide pyrophosphatase/phosphodiesterase 3 (ENPP3), prominin 1(PROM1) and plasminogen (PLG). Serum proteome analysis has unravelled the understanding on the mechanism of cholesterol reducing by F. deltoidea via augmentation of cholesterol biosynthesis that enhanced bile acids excretion, causing lowered cholesterol absorption in hypercholesterolemic rats.